Correlates of Occupational Heat-Induced Illness Costs: Case Study of South Australia 2000 to 2014. Issue 9 (September 2018) - Xiang, Jianjun; Hansen, Alana; Pisaniello, Dino; Dear, Keith; Bi, Peng
Abstract : Objective: To investigate the profile of occupational heat-induced illness costs in South Australia and to examine the association with high temperature. Methods: Workers' compensation claim data were used to quantify the associations between maximum temperature ( T max ) and occupational heat illness (OHI)-related costs, using time-series analysis after controlling for confounding factors. Results: Four hundred thirty-eight OHI claims in 2000 to 2014 resulted in total medical costs of AU$6, 002, 840 and 5, 036 work days lost. Relatively higher OHI burdens were found in men, those aged 25 to 44 years, new workers, medium-size businesses, and those employed in the mining industry. A 1 °C increase in T max above about 33 °C was associated with a 41.6% increase in medical costs and a 74.8% increase in days lost due to OHI, respectively. Conclusions: The cost profile of OHI may be used to justify interventions for particular industries, occupations, and worker categories. Abstract : Supplemental Digital Content is available in the text